Some threshold results and global stability of a host-mortal commensal ecological model with immigrated host species - Rao, N Seshagiri (Journal of Experimental Sciences, 2012)
The paper consists some threshold results on a Mathematical Model of a Host-Mortal Commensal Ecological Model with host is being harvested (Immigrated) at a constant rate by the identification of threshold regions through illustrations. Further, the global stability of this model with limited resources is established by Liapunov’s stability criteria. It is elicited by constructing a suitable Liapunov’s function for evaluating the global stability of the model in the case of co-existence equilibrium state. A pair of non-linear system of ordinary differential equations characterizes the model and the two equilibrium points are identified. Some threshold results are derived to establish the stability of the coexistent equilibrium state.